PENINGKATAN JARINGAN IRIGASI DAERAH IRIGASI KRIPIK KOTA SEMARANG - Muhamad Irvan; Nurwakhid Nurwakhid; Totok Apriyanto; Ratih Pujiastuti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
Water is a very basic need for All living things on this earth without exception. The Kripik River is currently not being utilized by community optimally. For this reason, it is necessary to increase Irrigation Area which aims to increase agricultural production. Currently, the Bendung Kripik area serves an irrigation area of 95,94 Ha with the height of the exsisting weir lighthouse is 1 m.The improvement of the irrigation network is carried out based on secondary data with other supporting data. The analysis carried out includes: hydrological analysis which includes : watershed, maximum rainfall, flood discharge, average rainfall, average climatology, Eto – Penman, F.J Mock mainstay discharge, planting patterns then carried out channel design, weir design and calculation of weir stability.In this study, it was proposed to increase the rice field area by 130.17 Ha From the results of hydrological analysis, the flood discharge value of the Nakayasu Synthetic Unit Hydrograph (HSS) method was obtained when repeating 100 th by 40.10 m3 / s. The water requirement for irrigation of D.I Kripik after the addition of the area is 0.086 m3 / s. As for the bed, a weir width of 30 m with a weir height of 1.05 m is required, a weir lighthouse width of 28 m, a rinse width of 1 m and a pillar width of 1 m (2 Pillars of 1 m each). The radius of the spherical threshold type weir is 0.5 m, the olak pond type is USBR Type IV with a length of 3.50m. Keywords: Irrigation, Weir, Flood Discharge